Coding the News: The role of computer code in filtering and distributing news. Issue 3 (16th March 2018) - Weber, Matthew S.; Kosterich, Allie
Abstract : This article examines the role of code in the process of news distribution and the degree to which code and algorithms can filter and prioritize news, much as an editor would. The discussion focuses specifically on the context of mobile news applications that filter news for consumers. Given concerns raised by the intersection of computer science and journalism, analysis moves away from the common notion that code is replacing humans as producers of news and shifts toward the role of code in helping journalists order and communicate the news. Thus, the focus of this research is on code as technological actants, filtering news based on decisions imbued into the code by human actors. This article reports the results of an investigation of code contained in 59 open source mobile news apps and an analysis of the content of that code. Findings highlight the journalistic decisions made in code and contribute to discussion surrounding the relationship between algorithmic and traditional news values.